Determining factors on technical instructors’ safety culture using structural analysis approach - Nor Kamilah Makhtar,; Balakrishnan Parasuraman,; Mohd Nazri Zakaria,; Ahmad Rasdan Ismail,; Satrya, Aryana (Penerbit Universiti Kebangsaan Malaysia, 2019)
Studies on safety culture have been increasing and several proposed models have been developed and evaluated to identify their key dimensions contributed to many occupational sectors. However, less of safety culture studies focused at education sector especially in Malaysia. This study aims to seek a deeper understanding of the structures of safety culture in Malaysian education sector mainly at Technical and Vocational Education Training (TVET). The objective also to investigate the relationship between psychological, behaviourial and situational dimension with safety culture, and to find out what can be done by the top management to increase safety culture in education sector. Data was collected from 391 Vocational Colleges’ (VC) instructor all over Malaysia that being selected using multistage sampling. Data was analyzed using SPSS 24 and SmartPLS-Structural Equation Modeling (SEM) technique. Partial least squares analysis revealed Influence of Peers, Safety Knowledge, Safety Communication, Safety Rules, Personnel Protective Equipment and Safety Training plays a pivotal role in inspiring the safety culture among the instructor. Assessment of Importance Performance Matrix Analysis (IPMA) showed that Safety Knowledge, Safety Rule, Influence of Peers and Safety Training are very important factors in determining a safety culture due to their relatively higher importance values compared to the rest of the variables. The study will help to improve safety culture in education sector and expected to bring in more safety awareness among instructor, which will inevitably bring in a culture of safe behavior. The ultimate result will be a substantial reduction or elimination in safety-related incidents and make an education sector as a safe workplace. Only a very few have examined the safety culture factors among VCs’ instructor as one of the TVET organisastion, and the used of Smart PLS is a novel idea, with the post analysis of IPMA gives an indicator to the top management of TVET’s education and Malaysia Ministry of Education (MOE) in build safety culture in this sector. Compliance of OSHA 1994 is seen as a good measure to build an education sector as a safe workplace.